Optical, Electrical and Structural Investigation on Different Molarities of Titanium Dioxide (TiO2) via Sol-Gel Method - Angelina, Harry; Marini, Sawawi; Muhammad, Kashif; Siti Kudnie, Sahari; Mohammad, Rusop (UTEM, 2017)
Titanium dioxide (TiO2) solution having different molarities were synthesized and deposited on glass substrates by using sol-gel spin-coating method. The variation in thickness, optical, electrical and structural properties of TiO2 thin films were investigated by surface profiler (SP), UV-Vis spectroscopy, two-point probes and atomic force microscopy (AFM), respectively. The result show that the thickness of TiO2 thin film increases as the molarities increases. The optical band gap energy decreases from 3.78 eV to 3.07 eV as the TiO2 molarities increases from 0.01M to 0.20M. The maximum value of the absorption coefficient was 16.27 x 104 cm-1 at 0.20M with surface roughness of 21.45 nm. Thin films deposited with 0.01M show lower absorption coefficient (3.87 x 104 cm-1) within visible region with surface roughness of 5.21 nm. The improvement in optical and structural properties of TiO2 thin films affects the electrical properties as the highest conductivity 9.62 x 102 S/m is obtained by 0.20M.